ANALISA PEMANFAATAN MULTIPROTOCOL LABEL SWITCHING PADA ROUTING PROTOCOL OPEN SHORTEST PATH FIRST - Friyanto, Angga; Bachtiar, Adam Mukharil; Baihaqi, Abdu Sofyan (Universitas Komputer Indonesia, 2020)
Digital transformation in various sectors has increased the need for network infrastructure to sustain high traffic. The availability of network resources is an important component in business processes in the digital era. Apart from adding infrastructure, a solution that can be done to meet these needs is optimization. OSPF (Open Shortest Path First) as a mechanism for determining the dynamic data transmission path has good features and performance by calculating automatically using an algorithm that calculates the bandwidth width. In data transmission, MPLS (Multiprotocol Label Switching) is a method of data transmission using labels in the process of forwarding data packets. This study analyzes the optimization of MPLS utilization as a data packet delivery mechanism for OSPF routing protocol communication. The analysis was carried out by comparing the data from the observation of the OSPF network system using MPLS and the OSPF network system without MPLS. From the analysis conducted by comparing the delay and packet loss, it is concluded that the network system using MPLS is more efficient and faster in data communication. Key Words : MPLS, OSPF, Routing, Traffic Engineering, Transmisi Data